2016
DOI: 10.1212/cpj.0000000000000265
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance for lumbar puncture

Abstract: Purpose of review: To review the literature and describe techniques to use ultrasound to guide performance of lumbar puncture (LP). Recent findings:Ultrasound evaluation of the lumbar spine has been shown in randomized trials to improve LP success rates while reducing the number of attempts and the number of traumatic taps. Summary: Ultrasound mapping of the lumbar spine reveals anatomical information that is not obtainable by physical examination, including depth of the ligamentum flavum, width of the intersp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 39 publications
2
46
0
4
Order By: Relevance
“…In both cases, X-ray fluoroscopy guidance is recommended and considered gold standard [2]. Several studies have reported that US-guided injections show no significant difference in diagnostic accuracy and therapeutic efficacy compared to guidance using fluoroscopy or CT, yet substantially reduce the radiation exposure of both patient and clinicians [3][4][5]. Nevertheless, the limited field of view and difficulties in interpreting US images are common obstacles to guarantee accurate needle placement [2].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, X-ray fluoroscopy guidance is recommended and considered gold standard [2]. Several studies have reported that US-guided injections show no significant difference in diagnostic accuracy and therapeutic efficacy compared to guidance using fluoroscopy or CT, yet substantially reduce the radiation exposure of both patient and clinicians [3][4][5]. Nevertheless, the limited field of view and difficulties in interpreting US images are common obstacles to guarantee accurate needle placement [2].…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the feedback on our article. 1 The recent randomized trial by Peterson et al 2 did not find a difference between landmark-based vs ultrasound-guided LP, but some important limitations must be recognized. Most important, the operators were residents with "varying degrees of experience performing ultrasound examinations, from no documented experience to over 100 documented examinations."…”
mentioning
confidence: 98%
“…
Torgovnick, MD: I read the article by Soni et al 1 line by line. Because of my association with a hospital at the epicenter of the AIDS epidemic, I have performed many thousands of lumbar punctures (LPs) for all of the usual reasons.
…”
mentioning
confidence: 99%
See 2 more Smart Citations